Off Track. - Meier, Deborah; Austen, Diane J. (Dissent (0012-3846))
Donald Trump has successfully promoted himself as the champion of people who feel unheard and unseen, including many minority and working-class voters. As a long-time educator, I (Deborah Meier) am particularly interested in how our public schools could be contributing to this phenomenon. Encouraged by Trump and his colleagues, many of those who support him express hostility toward those they perceive as the educated elite. (Although Trump received support from various sectors, an Edison Research poll has shown that Trump led Kamala Harris in the 2024 election by 24 points among non-college-educated men.) This hostility reminds me of the resentment I often witnessed as a public school principal and teacher in students who had scored poorly on standardized tests and had been assigned to low-ranked academic tracks. Students in the lower tracks frequently garner less respect, receive less positive attention from teachers, have narrower learning experiences, and as adults have lower earning power. These students grow into adults who feel left behind.